Interdisciplinary approach to unilateral missing maxillary lateral incisor with preparation modification (case report) - Mohamed Shaalan; Ibrahim Allam; Marwan Aggag (Advances in Medical, Pharmaceutical and Dental Research, 2024)
Background: In many clinical cases where one or both maxillary lateral incisors are absent, orthodontic treatment with space opening or closure using canine and premolar replacement has led to improved periodontal health and high patient satisfaction however with long treatment period. Preparation modification of the maxillary canine can simulate lateral incisor and first premolar can mimic the canine for appearance. Zirconia crowns have shown they can withstand occlusal and functional stresses while maintaining the required aesthetic appearance. Objectives: This case highlighted management of unilateral missing maxillary lateral incisor with only preparation modification using digital smile design and CAD- CAM technology.   Received: 14 July 2024 Accepted: 02 September 2024 Published: 19 September 2024